PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA KERJA, SELF LEARNING DAN KOMITMEN KERJA TERHADAP KINERJA GURU SMP NEGERI DI KOTA DEPOK, JAWA BARAT - Kailola, Lisa Gracia (Jurnal Dinamika Pendidikan, 2016)
ABSTRACTTeacherâs performance plays a crucial role in achieving quality of education and good character of students. Low teacherâs performance will decrease quality of graduates itself. Based on datas in Depok City, West Jawa, teacherâs performance is in priority programs of government, and still need to be increased. The obejctives of this research is to investigate whether there exists any direct positive effect of transormational leadership, work culture, self learning and work commitment towards teacherâs performance at State Junior High School in Depok City, West Java. A total of 91 from 974 teachers were sampled to collect data which was then analyzed using path analysis quantitative method. The result shows that there exists a positive direct effect of (1) transformational leadership towards teacherâs performance, (2) work culture towards teacherâs performance, (3) self learning towards teacherâs perfomance, (4) work commitment towards teacherâs performance, (5) transformational leadership towards work commitment, (6) work culture towards work commitment, (7) self learning towards work commitment, (8) transformational leadership towards self learning, (9) work culture towards self learning, and (10) transformational leadership towards work culture.Keywords: teacherâs performance, transformational leadership, work culture, self learning, work commitment.ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui apakah terdapat hubungan langsung positif kepemimpinan transformasional, budaya kerja, self learning, dan komitmen kerja terhadap kinerja guru SMP Negeri di Depok Jawa Barat. Sebanyak 91 dari 947guru digunakan sebagai sampel penelitian untuk memperoleh data yang kemudian dianalisis menggunakan metode kuantitatif analisis jalur.Hasil penelitian menunjukkan bahwa terdapat hubungan langsung positif (1) kepemimpinan transformasional terhadap kinerja guru, (2) budaya kerja terhadap kinerja guru, (3) self learning terhadap kinerja guru, (4) komitmen kerja terhadap kinerja guru, (5) kepemimpinan transformasional terhadap komitmen kerja, (6) budaya kerja terhadap komitmen kerja, (7) kepemimpinan transformasional terhadap self learning, (8) budaya kerja terhadap self learning, dan (9) kepemimpinan transformasional terhadap budaya kerja.Kata kunci: kinerja guru, kepemimpinan transformasional, budaya kerja, self learning, komitmen kerja